Effects of viral infection on biochemical protective reactions of wheat plants - Моlodchenkova Оlha; Mishchenko, Lidiya; Dunich, Alina; Rishchakova Оlha; Bezkrovnaya, Lidiya; Fanin, Yaroslav (ScienceRise: Biological Science, 2020)
The aim of the work – to investigate the influence of viral infection on the biochemical plant protective reactions Materials and methods of the research – The researches were conducted on wheat plants (Triticum aestivum L.) of the Julia variety of foreign plant breeding. Methods of the research: Biometrics, DAS-ELISA, Kjeldahl method, anthron method for the determination of sugars, spectrophotometric methods. The statistical analysis of experimental data was carried out using the program “Libre Office Calc”GNU Lesser General Public Licensev 3). Results of the researches. The obtained results indicate that some of the response of wheat plants to infection with wheat stripe mosaic virus (WSMV) is disturbances in the functioning of the photosynthetic apparatus of wheat leaves and a decrease in protein content. An increase of the soluble sugars and flavonoids content and activity of chitinase and β-1,3-glucanase at the affecting of WSMV was established. It may have a protective value. It was found, that the WSMV causes such nonspecific reactions of the plant cell as activation of lipid peroxidation and decrease of certain antioxidant enzymes (catalase et al.). It has been shown, that the activation of peroxidase, an increase of reduced glutathione content of cells, affected by WSMV, is the wheat plant protective reaction to the secondary oxidative stress that occurs in cells in the case of virus penetration. Conclusions. The study of the biochemical composition of wheat plants infected by WSMV, showed the presence of changes in some biochemical parameters which connected with the formation of plant defense mechanisms (content of photosynthetic pigments, protein, sugars, flavonoids, activity of PR proteins, intensity of oxidative and antioxidant processes). The obtained results can be used for selection of wheat varieties with economically valuable traits and complex resistance (both to climatic conditions of the environment and to phytoviral infections), which may be recommended for introduction into plant breeding and agricultural practice